Peace be with you! : my words to the church and to the world - Leo XIV, Pope, 1955- (HarperOne, an imprint of HarperCollins Publishers, 2026)
With his first public appearance before the world, Pope Leo XIV expressed hope for an 'unarmed and disarming' peace. Collected in a beautiful edition are the sermons and speeches Pope Leo XIV has delivered since his May 8, 2025, election. These initial addresses convey some of Pope Leo XIV's priorities: the primacy of God, communion in the Church, and the pursuit of peace. His countless calls for reconciliation are addressed not only to politics, but to the heart of every person.